CLIMATE CHANGE AND CHRONIC KIDNEY DISEASE - D.S.S.K.Raju; P. KIRANMAYI; Vijaya Rachel, K. (Asian Journal of Pharmaceutical and Clinical Research, 2014)
ABSTRACT BACKGROUND: The adverse effects of climate change are detrimental to health, wealth and economy of mostly the poor and low-income communities around the world. These climate changes have bearing on human health evidenced by increase in heat-related illnesses and deaths. It is well documented that acute renal failure is one of the complication in heat stress. All these factors eventually develop repeated subclinical renal dysfunction, which may further develop into chronic kidney disease (CKD). In India CKD is an increasing public health concern with poor outcome. METHODS: Renal insufficiency patients who are admitted during January2011 to December 2012 are selected; in this 198 patients with evidence of CKD were taken as cases. These CKD patients were admitted into Nephrology unit of MIMS hospital, Nellimarla. RESULTS AND CONCLUSION: In our study, most of the CKD (48.4%) cases are registered relatively high between the months of March and May. In the present study, creatinine clearance values using CG, MDRD and MCQE in CKD patients are significantly lowered when compared with control (p<0.001). In our study, most of the people registered are agricultural workers (24%), construction workers or laborers (23%) and industrial labor workers (19%) who belong to low income group. In the present investigation, it was observed that there was a progressive decline in GFR as the age advanced; these are more at risk of developing renal disease when exposed to heat stress. Keywords: climate change, chronic kidney disease, glomerular filteration rate